Study Habit and Test Anxiety as Determinants of Secondary School Students Performance in Social Studies - Ogunsanya, A. O.; Olayinka, Buraimo (NIU Journal of Humanities; Vol 5 No 1 (2020): KIU Journal of Humanities, Vol. 5 No. 1, March 2020, 2020)
This study examined study habit and test anxiety as determinants of secondary school studentâ€™s performance in Social Studies in Ogun State.  The study adopted a descriptive survey research design where structured and validated questionnaires were employed for data collection. 333 Junior secondary school students were selected using stratified sampling technique across four (4) secondary school in Ijebu-North Local Government Area of Ogun State. Three hypotheses were formulated and tested using regression analysis at 0.05 level. The findings showed that there is a significant influence of study habit on the academic performance of secondary school students in Social Studies. Findings also revealed that there is a significant influence of test anxiety on the academic performance of secondary school students in Social Studies. The result of the findings of this study further revealed that there is a significant composite influence of study habit and test anxiety on the academic performance of secondary school students in Social Studies. Based on the findings of this study, it was recommended among others; that regular counseling services should be introduced to the students in order to train them on study skills strategies which will enable them study harder in Social Studies. In addition, school authorities should work out guidelines as well as develop programmes that will help students to cope with test anxiety in Social Studies.